POSSIBILITIES OF DISTANCE EDUCATION IN THE CONDITIONS OF AN INFORMED LEGAL DEMOCRATIC SOCIETY (Proceedings of International Educators Conference, 2023)
In this article, comprehensive reforms carried out in the educational system of Uzbekistan, researches on the formation of organizational and legal bases of distance education, ensuring the right to education and organizing the educational process, the development of organizational and institutional mechanisms of distance education, the use of innovative pedagogical technologies, the credit-module system for education implementation, use of advanced methods of distance education with the help of modern information systems, ensuring the quality of education.